Overvejelser omkring princippperne for en syntaktisk-semantisk kontrastiv analyse af modalverberne i moderne engelsk og dansk - Lauridsen, Karen M. (HERMES - Journal of Language and Communication in Business, 1988)
The present paper deals with the principles of a syntactico-semantic constrastive analysis exemplified by the author's project concerning a semantic subcategorization of modality and a constrastive analysis has been established for the project along the following lines: the categories are defined as Boolean, imprecise categories, and the semantic categorization is established by means of a combination of, on the one hand, the distinction between epistemic and non-epistemic modality, and on the other hand, the modal operators possibility and necessity. The categories are thus defined by means of cross-linguistic logico-semantic criteria and are well suited as tertium comparationis in an analysis of language specific modal expressions such as the modal verbs.